Influence of environmental enrichment in captive chimpanzees (Pan troglodytes spp.) and gorillas (gorilla gorilla gorilla): behavior and faecal cortisol levels - Zaragoza, Félix; Ibáñez, Miguel; Mas, Blanca; Laiglesia, Santiago; Anzola, Bernadette (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
It is considered of significant importance to provide wild animals in captivity with environmental enrichment elements to improve their psychological and physiological well being, stimulating a higher activity and behavioral variety. This study evaluated the effect of different enrichment elements (explorative/manipulative, physical and feeding enrichment devices) on the behavior and physiology of two groups of great apes, gorillas (Gorilla gorilla) and chimpanzees (Pan troglodytes) at the Zoo-Aquarium of Madrid. The proposed prediction was that there would be a reduction of inactivity, anomalous and non-desired behavior, also on cortisol levels, as a result of the stimular improvements. The behaviors and cortisol faecal le- vels were compared between two different conditions: 1. previous phase without enrichment, 2. enrichment phase. The data analysis allowed measuring the efficiency of the enrichment, revealing that the frequency of inactivity and anomalous behaviors was significantly reduced in the enrichment phase. On the other hand, the frequency of exploratory-manipulative behavior increased in both species, whereas locomotors and feeding behaviors were reduced in gorillas but increased in chimpanzees. Also, the preferences of chimpanzees and gorillas for the diverse enrichments elements were different. In relation to the levels of cortisol, the results do not support the proposal for the initial hypothesis, both in the case of chimpanzees as in the case of gorillas, it had increased to such levels in the enrichment phase, the increase being significant just in the gorillas. The results on the behavioral parameters are consistent with the hypothesis because there is improvement induced by environmental enrichment.